The impact of digital learning technologies on students’ interest in mathematics: A systematic literature review - Muhammad Farel Wilenthino; Fiki Alghadari; Ade Kumalasari (S&Co Publishing, 2026)
Learning interest is a crucial psychological factor influencing students’ achievement in mathematics. However, numerous studies indicate that students’ interest in mathematics remains relatively low. The integration of digital technology in instruction has been widely explored as an alternative strategy to enhance learning interest, although previous studies have reported mixed findings. This study aims to synthesize previous research examining the effect of digital media and learning applications on students’ interest in mathematics. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Obtained 165 articles published and indexed by google scholar and then selected based on the keyword “interest in learning mathematics and digital technology”. The selection process resulted in 18 eligible articles published between 2020-2026, where the search was conducted in February 2026. The findings reveal that digital technology consistently has a positive impact on students’ learning interest, particularly in terms of attraction, enjoyment, and active engagement. Game-based media and interactive applications demonstrate the most significant effects. These findings imply that the integration of well-designed digital learning technologies can be an effective strategy for fostering students’ interest in mathematics, especially if supported by proper pedagogical planning and an interactive learning environment at every level of education. Nevertheless, most studies present methodological limitations and lack long-term impact evaluation.